Uhuru Kenyatta vs. The International Criminal Court: Narratives of Injustice & Solidarity - Hodgins, Stefanie (Université d'Ottawa | University of Ottawa, 2015)
The intent of this paper is to explore the dominant narratives used by Uhuru Kenyatta to discredit the legitimacy of the International Criminal Court within Kenya and Africa. Using a framing analysis as a theoretical approach, this paper identified four primary arguments, which pertained to issues of neo-colonialism, sovereignty, ethnic polarization, and national reconciliation. This paper argues that these arguments supported narratives of injustice and solidarity and were evoked by Kenyatta in order to mobilize a domestic and regional support base throughout the course of his trial at The Hague. This paper examines how these narratives were used in the context of the 2013 Kenyan election and at Kenyatta's various appearances at the African Union. Overall, this analysis offers new insights into the effectiveness of global criminal justice and considers the importance of addressing local perceptions and realities.